The Effectiveness of Nutrition Education on the Improvement of Iron Intake, Protein and Hemoglobin Levels Towards Zero Stunting At Amanah Deli Serdang Private Junior High School in 2022 - Sri Lasmawanti; Maya Ardilla Siregar; Maria Haryanti Butarbutar (Science Midwifery, 2022)
Profile of Medan City Health Office, anemia survey conducted in 4 districts/cities in North Sumatra, namely Medan City, Binjai, Kab. Deli Serdang, and Langkat it is known that 40.50% of women suffer from anemia. The stunting rate in 2019 was still at 27.67%. Meanwhile, based on data from the Ministry of Health's Basic Health Research, from 2013 to 2018 there was an increase in the prevalence of anemia in the 15-24 year age group, from 18.4% to 32% or 14.7 million people. The purpose of this study was to determine the effectiveness of nutrition on improving iron intake, protein and hemoglobin levels towards zero stunting in Amanah Deli Serdang Private Junior High School in 2022. This was a quantitative study, using a quasi-experimental design with one group pretest-posttest design. The population in this study were all students of SMP Amanah Deliserdang, the sample in this study was 28 grade 2 students. Iron intake showed that the p value = 0.015. the protein intake variable shows that the p value = 0.009, Based on the hemoglobin level variable the p value = 0.009 of the three variables shows that the p value < 0.05